Ответ:
отметьте ответ "лучший" пожалуйста
Объяснение:
1) х-у/4 × 6/у-х= х-у/2 × 3/-(х-у)= 1/2 ×(-3)= -3/2 — В.
2) (-ху/х+у)²= х²у²/х²+2ху+у²= х²у²/(х+у)² — А.
3) 1/х²-у² × х+у/1 =х+у/х²-у²= х+у/(х-у)(х+у)= 1/х-у — Д.
4) х²у-ху²/4ху × 8/х-у= ху(х-у)/ху × 2/х-у = 1×2=2 — Б
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
отметьте ответ "лучший" пожалуйста
Объяснение:
1) х-у/4 × 6/у-х= х-у/2 × 3/-(х-у)= 1/2 ×(-3)= -3/2 — В.
2) (-ху/х+у)²= х²у²/х²+2ху+у²= х²у²/(х+у)² — А.
3) 1/х²-у² × х+у/1 =х+у/х²-у²= х+у/(х-у)(х+у)= 1/х-у — Д.
4) х²у-ху²/4ху × 8/х-у= ху(х-у)/ху × 2/х-у = 1×2=2 — Б